2016
DOI: 10.1103/physrevlett.117.116601
|View full text |Cite|
|
Sign up to set email alerts
|

Glassy Dynamics in Disordered Electronic Systems Reveal Striking Thermal Memory Effects

Abstract: Memory is one of the unique qualities of a glassy system. The relaxation of a glass to equilibrium contains information on the sample's excitation history, an effect often refer to as "aging." We demonstrate that under the right conditions a glass can also possess a different type of memory. We study the conductance relaxation of electron glasses that are fabricated at low temperatures. Remarkably, the dynamics are found to depend not only on the ambient measurement temperature but also on the maximum temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Rather, the added crease length is determined only by the current total crease length and the new compaction depth. While processes that evolve logarithmically in time are readily observed in a variety of disordered physical systems, including stress or strain relaxation of a compacted sheet [17][18][19] , conductance relaxation of disordered electronic systems 20 , and creep dynamics of granular suspensions 21 , the emergence of a logarithmic model in the specific context of damage evolution in crumpled sheets is clearly distinct, and has had limited physical justification thus far.…”
mentioning
confidence: 99%
“…Rather, the added crease length is determined only by the current total crease length and the new compaction depth. While processes that evolve logarithmically in time are readily observed in a variety of disordered physical systems, including stress or strain relaxation of a compacted sheet [17][18][19] , conductance relaxation of disordered electronic systems 20 , and creep dynamics of granular suspensions 21 , the emergence of a logarithmic model in the specific context of damage evolution in crumpled sheets is clearly distinct, and has had limited physical justification thus far.…”
mentioning
confidence: 99%
“…Indeed in some of them, in the appropriate resistance range, these occur up to room temperature. [9][10][11] The technique can be very useful to analyze memory effects, and combined with conductance measurements, may shine light on the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…These glassy effects were first limited to low temperature T , but they have recently been observed at room temperature in discontinuous Au 9 , amorphous NbSi 10 and granular Al films 11 . In addition, high resolution techniques such as scanning force microscopy (SFM) open the possibility of studying these systems at room temperature allowing a detailed real space analysis of the problem.…”
Section: Introductionmentioning
confidence: 97%
“…In discontinuous metal films (gold, etc. ), a marked slowdown upon cooling was highlighted, giving rise to the formation of large frozen MDs [22,23,24]. More recently, we demonstrated that at low temperature the MD dynamics of granular Al films is thermally activated [25].…”
Section: Introductionmentioning
confidence: 91%
“…However, the T variation of the slow dynamics was found to be essentially of the Arrhenius type, with an activation energy of the order of 30 K which does not depend much on the resistance of the films. In discontinuous gold films, a different protocol has been used: the erasure of a MD formed at T 1 and during the cooling to T 2 is measured at T 2 and compared with the formation of a new isothermal MD at T 2 [22,23]. Signs of a strong temperature dependence of the dynamics are present since the MDs formed upon cooling between T 1 and T 2 cannot be significantly erased by subsequent V g changes at low temperatures, even after days of measurements.…”
Section: Arrhenius Law Hypothesismentioning
confidence: 99%